Electricity Demand Creation in Residential Sectors of Nepal - Adhikari, Shashwat; Jha, Ajay Kumar (Journal of Advanced College of Engineering and Management, 2024)
This research examines electricity demand in Nepal's residential sector, analyzing consumption patterns, demand-stimulation techniques, infrastructure challenges, affordability, and the consequences of rising demand. It emphasizes the need for sustainable growth through ongoing regulations, community involvement, and technology improvements. Nepal is transitioning to renewable energy but currently accounts for only 8.87% of total power use. The study uses the LEAP energy model to project electricity demand from 2021 to 2045 under various scenarios.